1990
DOI: 10.1210/jcem-71-1-223
|View full text |Cite
|
Sign up to set email alerts
|

H-Ras Protooncogene Mutations in Human Thyroid Neoplasms*

Abstract: Structural alterations of protooncogene sequences may be involved in the pathogenesis of human neoplasms. We screened 54 thyroid tumors (36 benign and 18 malignant) for gene rearrangements of the protooncogenes c-myc, c-myb, c-fos, c-erb-B1, c-erb-B2, c-erb-A, N-ras, K-ras, and H-ras. Only mutations of H-ras were observed. None of the 15 colloid adenomas examined had detectable H-ras rearrangements. Of the remaining tumors, we observed mutations of H-ras in 4 benign and 4 malignant neoplasms. Gene amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(54 citation statements)
references
References 38 publications
1
53
0
Order By: Relevance
“…They comprise a broad spectrum of neoplastic phenotypes, which include benign and nonprogressive macrofollicular adenomas, microfollicular adenomas, well-differentiated follicular and papillary carcinomas, and the invasive and always fatal anaplastic carcinomas (1). The sequence of somatic cell mutations which underlie these different tumor cell types is gradually becoming unraveled (2)(3)(4)(5)(6)(7)(8)(9). Activating point mutations of ras oncogenes are probably an early event in thyroid tumor formation, in that they occur with similar prevalence in benign and malignant thyroid tumors (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They comprise a broad spectrum of neoplastic phenotypes, which include benign and nonprogressive macrofollicular adenomas, microfollicular adenomas, well-differentiated follicular and papillary carcinomas, and the invasive and always fatal anaplastic carcinomas (1). The sequence of somatic cell mutations which underlie these different tumor cell types is gradually becoming unraveled (2)(3)(4)(5)(6)(7)(8)(9). Activating point mutations of ras oncogenes are probably an early event in thyroid tumor formation, in that they occur with similar prevalence in benign and malignant thyroid tumors (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of somatic cell mutations which underlie these different tumor cell types is gradually becoming unraveled (2)(3)(4)(5)(6)(7)(8)(9). Activating point mutations of ras oncogenes are probably an early event in thyroid tumor formation, in that they occur with similar prevalence in benign and malignant thyroid tumors (3)(4)(5)(6). Allelic losses ofchromosome 11 q 13, a region containing a number of genes involved in growth control, including the putative gene predisposing to multiple endocrine neoplasia type I, are found in follicular but not papillary thyroid tumors (7), suggesting that loss of a tumor suppressor gene at this locus may direct progression towards the follicular phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…114 The predominance of EGF receptor expression in papillary carcinoma was extended to the transcripts of c-erbB1 and c-erbB2/neu oncogenes which encode EGF receptor or analogue respectively. 115,116 Aasland et al 116 reported a two-to threefold increase in c-erbB1 and c-erbB2/neu mRNA in papillary carcinomas and their lymph node metastases, as well as in one benign adenoma compared to thyroid tissue.…”
Section: Egf and Egf Receptormentioning
confidence: 99%
“…115,117 EGF expression was shown to be of prognostic value in that tumors with higher EGF expression were more likely to recur. 113 as was suggested by Aasland et al 116 earlier on the basis of c-erbB1 and c-erbB2/neu expression.…”
Section: Egf and Egf Receptormentioning
confidence: 99%
“…Ras mutations are found at similar frequencies in benign adenomas and di erentiated carcinomas, suggesting that they are an initiating event in thyroid neoplasia (Lemoine et al, 1990;Namba et al, 1990;Suarez et al, 1990). The e ects of activated Ras on thyroid cells are exceedingly complex.…”
Section: Introductionmentioning
confidence: 99%